(3GdQSGdI GdcGTaI aj TQM MOjK (B" (3cfJ cfRG eNajG (B"s - (3GdTYhQj, GdHGdjcSQj, Ydj Hf Ydjs ((3MGaX Ydj GdTcQjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO def GLJHi Ke XgQ Ke GNJai hHYO ajbhd UHGM GdOjf GdTYhQj Ydj Hf Ydj GdHGdcSQj deG fXQJ aj bhd GdfHj cfJ cfRG eNajG aCMHHJ Cf GYQa aoNdbJ djYQahfj Cf CQJH QSGdI hSejJgG HGdcGTaIs
(3BNQgG (B:s
(3bhdg JYGdi (B: {(3nhndG nJnJnenqfrhG neG nanqVnd Gdnqdog pHpg nHrYnVocre nYndi nHrYmV(B} (3GdBjI , hgPg GdGeJjGR CeG ebJVGeG gjGJge hMbjbGJge hCeG ebJVG CaQLJge GdeNUhUI hCeG ebJVi NGUjI NdbgG Gddg JYGdi ajges
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf (B1 / 568s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds